A Risk-Based Security Governance Framework for Modern Information Systems - Okolie Awele, Saadat Oibiyeye, Abdulaziz O Ibiyeye, Didunoluwa Olukoya, (Journal of Computational Analysis and Applications (JoCAAA), 2026)
The major factors contributing to the increasing complexity of modern information systems are the use of cloud computing, distributed architectures, and integration of data from different organizations. These changes improve the efficiency and scalability of operations but at the same time also bring about security, operational, and regulatory risks which are very difficult to manage through the conventional security approaches that are control-centric. Most of the current information security governance models are not flexible enough to meet the demands of the constantly changing risk environments and the new system architectures. This paper introduces a risk-based security governance framework that would facilitate modern information systems to make structured, transparent, and adaptive decisions. The framework is built around the principles of risk identification, risk assessment, and risk prioritization coupled with governance-level monitoring and control alignment. The proposed approach fosters organizations to convert complex risk environments into governance decisions with the help of risk context, accountability, and continuous observation